Protecting personnel at hazardous waste sites - Martin, William F.; Levine, Steven P. (Butterworth-Heinemann, 1994)
REFERENCES; Chapter 7. Medical Surveillance for Hazardous Waste Workers; PREEMPLOYMENT SCREENING; PERIODIC SCREENING; ACUTE OR EPISODIC MEDICAL CARE; RECORDKEEPING AND PROGRAM REVIEW; CONCLUSION; PREEMPLOYMENT SCREENING; PERIODIC SCREENING; ACUTE MEDICAL CARE; RECORDKEEPING AND PROGRAM REVIEW; REFERENCES; Chapter 8. Site Layout and Engineered Controls; SITE LAYOUT; CONTROL ZONES; AREA DIMENSIONS; CONTAMINATION CONTROL; ENGINEERED CONTROLS; SITE PREPARATION; ISOLATION AND CONTAINMENT BARRIERS; SPECIAL EQUIPMENT; WARNING ALARMS AND DEVICES; AIR POLLUTION CONTROL